2017
DOI: 10.1097/ncc.0000000000000357
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Determinants of Port Occlusions in Cancer Outpatients

Abstract: Nurses play a key role in maintaining a functioning port using positive pressure during the flushing techniques. Certain risk factors must be monitored to prevent partial occlusions, and certain patients are more likely to present with port-related problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
0
5
0
4
Order By: Relevance
“…It has been reported that heparin treatment produced heparin-induced thrombocytopenia (HIT) in seriously ill patients [7]. Additionally, it is estimated that the occlusion rate is between 0 and 33% when using HS solution [8, 9]. Therefore, the risk of heparin exposure should also be emphasized.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that heparin treatment produced heparin-induced thrombocytopenia (HIT) in seriously ill patients [7]. Additionally, it is estimated that the occlusion rate is between 0 and 33% when using HS solution [8, 9]. Therefore, the risk of heparin exposure should also be emphasized.…”
Section: Introductionmentioning
confidence: 99%
“…Con el total de 4111 observaciones, 54 obstrucciones parciales (OP) fueran documentadas. Como resultado principal, se constató un incremento significativo de la tasa OP (p<0,001) en catéteres que obtuvieron al menos una recogida de sangre (15) .…”
Section: Discusión Estrategias De Prevención De La Obstrucción En Cvc-tiunclassified
“…Sin embargo, cuando el grupo analizó separadamente los catéteres que no pasaron por el procedimiento de recogida de sangre, la OP se mostró más frecuente (p<.0001) en catéteres que obtuvieran al menos una recogida de sangre (15) .…”
Section: Discusión Estrategias De Prevención De La Obstrucción En Cvc-tiunclassified
“…A obstrução é uma complicação mecânica, decorrente da oclusão parcial ou total do cateter devido as causas trombótica ou não trombótica. É evidenciada pela dificuldade ou ausência de refluxo de sangue pelo cateter aquando da aspiração de sangue intralúmen, e/ou pela impossibilidade de administrar medicamentos e soluções pelo cateter (Milani et al, 2017;Pedreira, 2015). Como causas da obstrução do CVC citamse a precipitação intralúmen de lipídios ou medicamentos, a presença de coágulo sanguíneo no interior do cateter e problemas mecânicos, como o mau posicionamento do cateter ou dobras (van Miert, Hill, Jones, 2013).…”
Section: Introductionunclassified